Low-radioactivity spherical aluminum oxide as well as preparation method and application thereof

By using ultrapure water and acid solution to disperse raw materials in the preparation of alumina, and using alkaline anion exchange resin to remove radioactive elements, combined with high-temperature insulation and melt spheroidization, the problems of complex processes and radioactive contamination in the prior art are solved. , realizes the preparation of alumina products with low radioactivity and high thermal conductivity, suitable for the high filling and thermal conductivity requirements of EMC.

CN119490209APending Publication Date: 2025-02-21YAAN BESTRY PERFORMANCE MATERIALS CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411655934.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art has complex processes when preparing low-radioactive alumina, which is not suitable for large-scale production, and the radioactive elements are not completely separated, which has the problem of radioactive contamination of water bodies. The obtained alumina products are difficult to meet the requirements of high thermal conductivity and low radioactivity.

Method used

The raw material is dispersed with ultrapure water and acid solution at 20~60℃, alkaline anion exchange resin is added for hydrothermal treatment, radioactive elements are removed, and then high-temperature insulation treatment and melt spheroidization are carried out to obtain low-radioactive spherical alumina. This method uses alkaline anion exchange resin to remove uranium by controlling the water temperature and pH value, ensuring low radioactivity and high thermal conductivity of the product.

Benefits of technology

The preparation of low-radioactive spherical alumina has been achieved, with a uranium content of <3 ppb and a high thermal conductivity. It is suitable for high filling and thermal conductivity of EMC, and the process is simple and controllable, and is suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490209A_ABST
    Figure CN119490209A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic powder, and discloses low-radioactivity spherical aluminum oxide as well as a preparation method and application thereof. The preparation method comprises the following steps: adopting ultrapure water at 20-60 DEG C, and adding acid to adjust the pH value to be less than or equal to 2.5 to obtain acid liquor; taking aluminum hydroxide / boehmite / industrial alumina as raw materials, adding the raw materials into the acid liquor, and stirring and dispersing to obtain mixed slurry A; adding alkaline anion exchange resin into the mixed slurry A, carrying out hydrothermal stirring treatment for 8-12 hours, and removing the alkaline anion exchange resin to obtain mixed slurry B; carrying out suction filtration and drying on the mixed slurry B, and carrying out heat preservation treatment on the dried material at 1300-1400 DEG C for 6-9 hours; and S4, crushing and dispersing the material subjected to heat preservation treatment in the step S4, and melting and spheroidizing at 1100-1300 DEG C to obtain a low-radioactivity spherical aluminum oxide crude product. The prepared low-radioactivity spherical alumina powder is compact in structure, high in thermal conductivity, low in uranium content and suitable for EMC production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic powders, and in particular relates to low-radioactive spherical alumina and a preparation method and application thereof. Background Art

[0002] Epoxy molding compound (EMC) is widely used in the field of chip packaging. However, with the development of stacked packaging technology, the high density of chips has put forward higher requirements for EMC packaging materials. This requires EMC to have higher thermal conductivity, and at the same time, the maximum particle size of the filler in EMC must be strictly controlled to prevent large particles from causing irreversible damage to the chip. On the other hand, if the filler in EMC contains high levels of radioactive elements (thorium and uranium), it will emit alpha rays, causing the risk of soft errors in CPU operation. Therefore, it is of great significance to develop low-alpha ray alumina as EMC filler.

[0003] The existing technology for preparing low-radioactive alumina has the problem of complex process and is not suitable for large-scale production and application; there are also problems such as incomplete separation of radioactive elements and radioactive contamination of water bodies in the preparation process; the obtained alumina products are difficult to meet the EMC requirements of improving thermal conductivity through high filling, etc. Summary of the invention

[0004] In view of the shortcomings of the above-mentioned prior art, the present invention provides a low-radioactive spherical alumina and a preparation method and application thereof. The alumina prepared by the preparation method has a uranium content of less than 3 ppb, low radioactivity, is suitable for EMC use, has a high filling rate and high thermal conductivity, and the preparation method is suitable for industrial-scale production and is environmentally friendly.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A low-radioactive spherical alumina, wherein the powder of the low-radioactive spherical alumina is α-alumina, the uranium content is less than 3 ppb, the spheroidization rate is ≥95%, and the true density is ≥3.65 g / cm 3 ; Particle size D50 is 4.5~50 μm.

[0007] Furthermore, the powder particle size distribution of the low-radioactive spherical alumina has at least two peaks.

[0008] Furthermore, the maximum breaking particle size of the low-radioactive spherical alumina powder is less than 75 μm, and the particle size distribution D50 is 10-30 μm.

[0009] A method for preparing low-radioactive spherical alumina comprises the following steps:

[0010] S1, using ultrapure water at 20-60°C, adding acid to adjust the pH to ≤ 2.5, to obtain an acid solution;

[0011] S2, taking aluminum hydroxide / boehmite / industrial alumina as raw materials, adding them into the acid solution, stirring and dispersing, and obtaining a mixed slurry A;

[0012] S3, adding a basic anion exchange resin to the mixed slurry A, hydrothermally stirring for 8 to 12 hours, removing the basic anion exchange resin, and obtaining a mixed slurry B;

[0013] S4, filtering and drying the mixed slurry B, and heat-treating the dried material at 1300-1400° C. for 6-9 h;

[0014] S5, crushing and dispersing the material after the heat preservation treatment in step S4, melting and spheroidizing at 1100-1300°C to obtain a crude low-radioactive spherical alumina product.

[0015] Furthermore, the method further comprises step S6, wherein the crude low-radioactive spherical alumina product is subjected to airflow classification to obtain powders of various different cut-off particle sizes, and the powders of various different cut-off particle sizes are mixed and graded to obtain the desired low-radioactive spherical alumina product.

[0016] Furthermore, the raw material is industrial aluminum hydroxide, and the mass ratio of the industrial aluminum oxide to the ultrapure water is 5-6:8-10.

[0017] Furthermore, the uranium content in the industrial alumina is ≤40 ppb, and the particle size D50 is 0.5-45 μm; the industrial alumina is mainly γ-alumina.

[0018] Furthermore, the alkaline anion exchange resin is a quaternary ammonium anion exchange resin; the addition ratio of the alkaline anion exchange resin to the alumina / boehmite / industrial alumina is 1-3:100.

[0019] Furthermore, in step S3, the alkaline anion exchange resin is loaded into a filter bag / porous container and then put into the mixed slurry A for hydrothermal stirring treatment. After the treatment is completed, the filter bag / porous container loaded with the alkaline anion exchange resin is taken out to obtain a mixed slurry B.

[0020] Further, in step S6, three kinds of powders with a maximum breaking particle size of 25 μm and a D50 of 5.0-5.5 μm, a maximum breaking particle size of 53 μm and a D50 of 20-25 μm, and a maximum breaking particle size of 75 μm and a D50 of 40-45 μm are compounded in a mass ratio of 7:2:1 to obtain the desired low-radioactive spherical alumina product.

[0021] Application of low-radioactive spherical alumina prepared by the method for preparing low-radioactive spherical alumina as described in any one of the above in EMC.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The method for preparing low-radioactive spherical alumina of the present invention is to control the water temperature and adjust the pH to ≤ 2.5, then add the raw materials for mixing, and perform hydrothermal treatment with alkaline anion exchange resin to achieve the removal of radioactive elements; then the filtered and dried materials are subjected to heat preservation treatment for a certain period of time to achieve crystal phase transformation and eliminate the loose and porous characteristics of gamma alumina, obtain α-phase alumina with a denser structure, and improve thermal conductivity; then crush and melt spheroidize to ensure that low-radioactive, α-phase, dense, and high-sphericity alumina is obtained. The preparation process of this method is simple and controllable, suitable for large-scale production, and the obtained alumina product is α-phase, with a dense structure, high particle density, high thermal conductivity, and low radioactivity, which is suitable for EMC production applications.

[0024] 2. By selecting industrial alumina, mainly γ-alumina, as raw material, taking advantage of its loose and porous structure, and controlling its particle size, the uranium (U) content of the raw material, and the addition ratio range of the alkaline anion exchange resin, it can be effectively ensured that alumina products with extremely low uranium content can be obtained through ion exchange; and high-temperature insulation treatment is carried out before melt spheroidization to eliminate the influence of the loose and porous structure on the product, so as to obtain a dense product with high thermal conductivity.

[0025] 3. After the spherical alumina powder of the present invention is treated by airflow classification, the mixing and grading is carried out according to different cut-off particle sizes. The obtained low-radioactive spherical alumina product has a controllable maximum particle size and a high true density. It has a high thermal conductivity for preparing EMC products, has a low risk of radiation influence, and is safer and more reliable.

[0026] 4. The alkaline anion exchange resin is placed in a filter bag / porous container and then put into the mixed slurry A for hydrothermal stirring treatment. After the treatment is completed, it can be directly taken out, thereby avoiding the problem of difficult separation and removal caused by the alkaline anion exchange resin directly mixing with the material. The obtained product has high purity and is not prone to residual alkaline anion exchange resin impurities. The alkaline anion resin that adsorbs radioactive elements is easy to recover and centrally treat, avoiding direct discharge to pollute the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is the SEM image of the material on the 600-mesh sieve of sample 1 prepared in Example 1.

[0029] Figure 2 This is the SEM image of the material on the 300-mesh sieve of Sample 2 prepared in Example 2.

[0030] Figure 3 This is the SEM image of the material on the 230-mesh sieve of Sample 3 prepared in Example 3.

[0031] Figure 4 The particle size diagram of samples 1, 2, and 3.

[0032] Figure 5 This is the particle size diagram of the product in Example 4. DETAILED DESCRIPTION

[0033] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0034] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0035] The embodiment of the present invention provides a low-radioactive spherical alumina and a preparation method and application thereof, the method comprising the following steps:

[0036] S1, using 20~60℃ ultrapure water, adding acid to adjust the pH to ≤2.5, to obtain acid solution.

[0037] Specifically, a certain volume of ultrapure water is added to the reaction kettle, the temperature is controlled at 20-60° C., sulfuric acid / hydrochloric acid / nitric acid is added to adjust the pH to ≤ 2.5 to obtain the desired acid solution. Preferably, sulfuric acid is used to adjust the pH.

[0038] Controlling the water temperature within this range for the dispersion and ion exchange of raw materials can effectively improve the ion removal efficiency. Adjusting and controlling the pH to ≤ 2.5, preferably controlling the pH to 1.0-2.5 for ion exchange to remove radioactive elements, has a higher removal efficiency; under this acidic pH condition, the radioactive element uranium mainly exists in the form of uranyl ions, which can be better adsorbed and removed by alkaline anion exchange resin in subsequent treatment; and when the pH is greater than 2.5, the uranyl ions are hydrolyzed, and there will be a polymerization reaction to form a multi-core or even cage-like structure, and finally a hydroxide precipitate is generated, which affects the removal of uranium ions.

[0039] S2, taking aluminum hydroxide or boehmite or industrial alumina as a raw material, adding it into the acid solution prepared in step S1, fully stirring and dispersing, and obtaining a mixed slurry A.

[0040] Preferably, industrial alumina is selected as a raw material and added into an acid solution for stirring and dispersion to prepare a mixed slurry A. Aluminum hydroxide and boehmite contain high water content and have a problem of low yield.

[0041] S3, adding alkaline anion exchange resin to the mixed slurry A prepared in step S2, and subjecting the mixed slurry to hydrothermal stirring treatment for 8-12 hours, the hydrothermal temperature being 20-60° C., preferably 30-50° C., and removing the alkaline anion exchange resin after the treatment to obtain a mixed slurry B.

[0042] Among them, the alkaline anion exchange resin is preferably a quaternary ammonium anion exchange resin, which has the advantages of multiple reaction sites, strong activity, and high efficiency in removing radioactive elements.

[0043] S4, filtering and drying the mixed slurry B obtained in step S3, and heat-treating the dried material at 1300-1400°C for 6-9 hours. Heat-treating at this temperature for 6-9 hours can achieve complete transformation of the crystal phase and eliminate the loose and porous structure of gamma alumina, so as to obtain a more compact α-phase alumina and improve the thermal conductivity of subsequent products.

[0044] S5, crushing and dispersing the material after the heat preservation treatment in step S4, which can be crushed and dispersed by air flow crushing and dispersion or jaw crushing, and the crushed and dispersed material is put into a melting spheroidizing furnace, melted and spheroidized at 1100-1300°C, and low-radioactive spherical alumina crude product can be obtained after spheroidization.

[0045] In a further embodiment, step S6 is also included, wherein the low-radioactive spherical alumina obtained after the melt spheroidization in step S5 is subjected to airflow classification treatment to obtain powders of various different cut-off particle sizes, and then the powders of various specific cut-off particle sizes are mixed and graded in a certain proportion as needed to obtain the desired low-radioactive spherical alumina product. The composite low-radioactive spherical alumina product has a large tap density and has a higher filling rate and better thermal conductivity when used in the preparation of EMC.

[0046] Preferably, the classification frequency of the airflow classification is 10-30 Hz, and a low-radioactive spherical alumina powder product with a desired cut-off particle size can be obtained.

[0047] Furthermore, after air flow classification, sieves of the required particle size are used for sieving (100% complete sieving or the sieve underflow is taken as the required powder) to ensure that the maximum cutoff particle size of the powders with different cutoff particle sizes obtained is less than or equal to the target cutoff particle size.

[0048] Preferably, the mass ratio of the added amount of the raw material (aluminum hydroxide or boehmite or industrial alumina) to ultrapure water is controlled to be 5-6:8-10. In particular, when industrial alumina is used as the raw material, the mass ratio of industrial alumina to ultrapure water is controlled to be 5-6:8-10, and the obtained mixed slurry A has an appropriate concentration, ensuring a high subsequent radioactive element removal rate and good economic efficiency.

[0049] Preferably, the addition ratio of the basic anion exchange resin to the raw material (alumina / boehmite / industrial alumina) is controlled to be 1-3:100.

[0050] It was found during production that when the addition ratio of alkaline anion exchange resin is too low, less than 1:100, the removal effect of radioactive elements is not ideal; and when the addition ratio of alkaline anion exchange resin is too high, exceeding 3:100, the removal effect of radioactive elements is not significantly improved, but there is a waste of materials and uneconomical problems.

[0051] It is further preferred to select industrial alumina with a uranium content of ≤40 ppb as the raw material, control the particle size D50 within the range of 0.5~45 μm, and select industrial alumina with γ-phase alumina as the main crystal phase as the raw material. The raw material with γ-phase alumina as the main crystal phase has a loose and porous structure, which is conducive to the release of uranium ions and their adsorption and removal by alkaline anion exchange resin, and the removal efficiency is high. At the same time, it is found that when the uranium content of the raw material exceeds 40 ppb, the processing cost will be significantly increased, such as greatly increasing the amount of alkaline anion exchange resin added and greatly increasing the hydrothermal stirring treatment time to achieve the corresponding treatment effect, and the economic efficiency is low. By controlling the structure of the raw material, as well as the range of uranium content and particle size, it can be further ensured that low-radioactive alumina is obtained with high comprehensive economic efficiency.

[0052] The low-radioactive spherical alumina product prepared by this method has a spheroidization rate of ≥95% and a true density of ≥3.65 g / cm 3 ; Particle size D50 is in the range of 4.5~50 μm; Radioactive uranium content is less than 3 ppb, and even the uranium content can be less than 1 ppb. When used to prepare EMC, it has good fluidity and high density, which is beneficial to improve the thermal conductivity of EMC products.

[0053] Further preferably, when performing step S3, the alkaline anion exchange resin is placed in a filter bag or a porous container, and then put into the mixed slurry A for hydrothermal stirring treatment. After the hydrothermal stirring treatment is completed, the filter bag or porous container containing the alkaline anion exchange resin is directly taken out to obtain the mixed slurry B. The porous container can be a porous acid-resistant plastic barrel, and its pore size is smaller than the particle size of the alkaline anion exchange resin.

[0054] The alkaline anion exchange resin is placed in a filter bag or a porous container for ion exchange treatment, which can effectively avoid the problem of ion exchange resin settling in the material and being difficult to separate and remove, and facilitates the separation and recovery of the alkaline anion exchange resin adsorbing radioactive elements for centralized treatment after the reaction is completed. At the same time, it can avoid the problem of ion exchange resin adsorbing radioactive elements remaining in the material, which causes the radioactive elements to be discharged with the washing water during filtration.

[0055] The frequency of airflow classification is controlled to obtain powders with different cut-off particle sizes, and a maximum particle size quantification method is used to sieve powders with a variety of required maximum cut-off particle sizes, which is convenient for accurate quantification and control of the maximum cut-off particle size of the prepared low-radioactive spherical alumina, thereby better meeting the high particle size requirements of EMC fillers.

[0056] Preferably, three kinds of powders with a maximum breaking particle size of 25 μm and a D50 of 5.0-5.5 μm, a maximum breaking particle size of 53 μm and a D50 of 20-25 μm, and a maximum breaking particle size of 75 μm and a D50 of 40-45 μm are obtained, and the three kinds of powders are compounded in a mass ratio of 7:2:1 to obtain a composite low-radioactive spherical alumina product with a D50 of about 20-25 μm and a high true density. When used as an EMC filler, the product has a high thermal conductivity (up to 3.65 W / (mK)) and is not easy to damage the chip.

[0057] Among them, the maximum particle size quantification method is: select 200g of the prepared low-radioactive spherical alumina product, select the sieve T1 with appropriate mesh number according to the maximum single particle size requirement, and require the product to be 100% screened; then select the sieve T2 with a mesh number larger than that of sieve T1, the product is screened through sieve T2, and the product on the sieve is tested by scanning electron microscopy (SEM) to pull out the maximum particle size. If the maximum particle size is smaller than the aperture represented by sieve T1, the aperture of sieve T1 is the maximum cut-off particle size.

[0058] Example 1

[0059] 800 L of ultrapure water was added to the reactor, the water temperature was controlled at about 40°C, and the pH was adjusted to 2.0 using sulfuric acid; then 500 kg of commercially available industrial alumina was added to the reactor as a raw material and fully stirred and dispersed to obtain a mixed slurry A-1. The industrial alumina has γ-alumina as the main crystal phase, and its uranium content was 38.57 ppb and its particle size D50 was 5.23 μm.

[0060] 5 kg of alkaline anion exchange resin was loaded into a porous plastic drum (the pore size of the porous plastic drum was smaller than the particle size of the alkaline anion exchange resin), and the porous plastic drum containing the alkaline anion exchange resin was put into the mixed slurry A-1 (the mass ratio of the alkaline anion exchange resin to the raw material industrial alumina was 1:100), and hydrothermally stirred, maintaining the solution temperature at about 40°C. After continuous stirring and reaction for 8 hours, the porous plastic drum containing the alkaline anion exchange resin was taken out (for recovery and centralized treatment) to obtain a mixed slurry B-1.

[0061] The mixed slurry B-1 was filtered and dried, and the dried material was kept at 1300℃ for 6 hours, and then naturally cooled to room temperature. Then the material was dispersed by air flow crushing, and the crushed material was put into a melting spheroidizing furnace for melting spheroidization. The temperature of the melting zone was controlled at about 1123℃. The product after melting spheroidization was classified by an air flow classification system, and the classification frequency was controlled to be 30Hz. It was sieved through a 500-mesh screen to obtain sample 1.

[0062] The particle size and uranium content of sample 1 were tested, and the results are shown in Table 1 and Figure 4 As shown; take sample 1 through a 600-mesh sieve, take the sample on the sieve for electron microscopy, the result is as follows Figure 1 shown.

[0063] Example 2

[0064] 800 L of ultrapure water was added to the reactor, the water temperature was controlled at about 40°C, and sulfuric acid was used to adjust the pH to 2.0; then 600 kg of commercially available industrial alumina was added to the reactor as a raw material and fully stirred and dispersed to obtain a mixed slurry A-2. The industrial alumina has γ-alumina as the main crystal phase, and its uranium content is 32.33 ppb and the particle size D50 is 21.46 μm.

[0065] 18 kg of alkaline anion exchange resin was loaded into a porous plastic drum (the pore size of the porous plastic drum was smaller than the particle size of the alkaline anion exchange resin), and the porous plastic drum containing the alkaline anion exchange resin was put into the mixed slurry A-2 (the mass ratio of the alkaline anion exchange resin to the raw material industrial alumina was 3:100), and the solution was stirred hydrothermally while maintaining the solution temperature at about 40°C. After continuous stirring and reaction for 10 hours, the porous plastic drum containing the alkaline anion exchange resin was taken out (for recovery and centralized treatment) to obtain a mixed slurry B-2.

[0066] The mixed slurry B-2 was filtered and dried, and the dried material was kept at 1350℃ for 8 hours, and then naturally cooled to room temperature. The material was then crushed and dispersed by jaw crusher, and the crushed material was put into a melting spheroidizing furnace for melting spheroidization. The temperature of the melting zone was controlled at about 1256℃. The product after melting spheroidization was classified by an airflow classification system, and the classification frequency was controlled to be 22Hz. It was sieved through a 270-mesh screen to obtain sample 2.

[0067] The particle size and uranium content of sample 2 were tested, and the results are shown in Table 1 and Figure 4 As shown; take sample 2 through a 300-mesh sieve, take the sample on the sieve for electron microscopy, the result is as follows Figure 2 shown.

[0068] Example 3

[0069] 800 L of ultrapure water was added to the reactor, the water temperature was controlled at about 40°C, and sulfuric acid was used to adjust the pH to 2.0; then 600 kg of commercially available industrial alumina was added to the reactor as a raw material and fully stirred and dispersed to obtain a mixed slurry A-3. The industrial alumina has γ-alumina as the main crystal phase, and its uranium content is 36.68 ppb and the particle size D50 is 42.45 μm.

[0070] 12 kg of alkaline anion exchange resin was loaded into a porous plastic drum (the pore size of the porous plastic drum was smaller than the particle size of the alkaline anion exchange resin), and the porous plastic drum containing the alkaline anion exchange resin was put into the mixed slurry A-3 (the mass ratio of the alkaline anion exchange resin to the raw material industrial alumina was 2:100), and the solution was stirred hydrothermally while maintaining the solution temperature at about 40°C. After continuous stirring and reaction for 10 hours, the porous plastic drum containing the alkaline anion exchange resin was taken out (for recovery and centralized treatment) to obtain a mixed slurry B-3.

[0071] The mixed slurry B-3 was filtered and dried, and the dried material was kept at 1350℃ for 8 hours, and then naturally cooled to room temperature. The material was then crushed and dispersed by jaw crusher, and the crushed material was put into a melting spheroidizing furnace for melting spheroidization. The temperature of the melting zone was controlled at about 1250℃. The product after melting spheroidization was classified by an airflow classification system, and the classification frequency was controlled to be 10 Hz. It was sieved through a 200-mesh screen to obtain sample 3.

[0072] The particle size D and uranium content of sample 3 were tested, and the results are shown in Table 1 and Figure 4 As shown; take sample 3 through a 230-mesh sieve, take the sample on the sieve for electron microscopy, the result is as follows Figure 3 shown.

[0073] Example 4

[0074] Sample 1, sample 2 and sample 3 were mixed and compounded in a mass ratio of 7:2:1, and mixed in a mixer for 30 min to obtain sample 4, which is a low-radioactive spherical alumina composite product with multiple particle size peaks. The particle size and uranium content of sample 4 were tested, and the results are shown in Table 1 and Figure 5 shown.

[0075] Comparative Example 1

[0076] 800 L of ultrapure water was added to the reactor, the water temperature was controlled at about 40°C, and the pH was adjusted to 2.0 using sulfuric acid; then 500 kg of commercially available industrial alumina was added to the reactor as a raw material and fully stirred and dispersed to obtain a mixed slurry A-d1. The industrial alumina has γ-alumina as the main crystal phase, and its uranium content was 37.66 ppb and its particle size D50 was 5.32 μm.

[0077] 4.5 kg of alkaline anion exchange resin was loaded into a porous plastic drum (the pore size of the porous plastic drum was smaller than the particle size of the alkaline anion exchange resin), and the porous plastic drum containing the alkaline anion exchange resin was put into the mixed slurry A-d1 (the mass ratio of the alkaline anion exchange resin to the raw material industrial alumina was 0.9:100), and hydrothermally stirred, maintaining the solution temperature at about 40°C. After continuous stirring and reaction for 8 hours, the porous plastic drum containing the alkaline anion exchange resin was taken out (for recovery and centralized treatment) to obtain a mixed slurry B-d1.

[0078] The mixed slurry B-d1 was filtered and dried, and the dried material was kept at 1300℃ for 6 hours, and then naturally cooled to room temperature. Then the material was dispersed by air flow crushing, and the crushed material was put into the melting spheroidization furnace for melting spheroidization. The temperature of the melting zone was controlled at about 1129℃. The product after melting spheroidization was classified by the air flow classification system, and the classification frequency was controlled to be 30 Hz. It was sieved through a 500-mesh screen to obtain comparative sample 1.

[0079] The particle size D50 and uranium content of comparative sample 1 were tested, and the results are shown in Table 1.

[0080] Comparative Example 2

[0081] 800 L of ultrapure water was added to the reactor, the water temperature was controlled at about 40°C, and the pH was adjusted to 2.65 using sulfuric acid; then 600 kg of commercially available industrial alumina was added to the reactor as a raw material and fully stirred and dispersed to obtain a mixed slurry A-d2. The industrial alumina has γ-alumina as the main crystal phase, and its uranium content was 31.67 ppb and the particle size D50 was 21.67 μm.

[0082] 18 kg of alkaline anion exchange resin was loaded into a porous plastic drum (the pore size of the porous plastic drum was smaller than the particle size of the alkaline anion exchange resin), and the porous plastic drum containing the alkaline anion exchange resin was put into the mixed slurry A-d2 (the mass ratio of the alkaline anion exchange resin to the raw material industrial alumina was 3:100), and hydrothermally stirred, maintaining the solution temperature at about 40°C. After continuous stirring and reaction for 10 hours, the porous plastic drum containing the alkaline anion exchange resin was taken out (for recovery and centralized treatment) to obtain a mixed slurry B-d2.

[0083] The mixed slurry B-d2 was filtered and dried, and the dried material was kept at 1350℃ for 8 hours, and then naturally cooled to room temperature. The material was then crushed and dispersed by jaw crusher, and the crushed material was put into a melting spheroidizing furnace for melting spheroidization. The temperature of the melting zone was controlled at about 1248℃. The product after melting spheroidization was classified by an airflow classification system, and the classification frequency was controlled to be 22 Hz. It was sieved through a 270-mesh screen to obtain comparative sample 2.

[0084] The particle size D50 and uranium content of comparative sample 2 were tested, and the results are shown in Table 1.

[0085] Test Case

[0086] Samples 1-4 and comparative samples 1-2 were respectively configured as EMC samples with a filling rate of 88%, and the thermal conductivity of the EMC samples was tested. The test results are shown in Table 1.

[0087] Table 1 Test results of samples and configured EMC samples of Examples 1-4 and Comparative Examples 1-2

[0088] serial number D50 (μm) Uranium (U) content (ppb) Maximum particle size (μm) Screening rate (%) Thermal conductivity (W / (mK)) Sample 1 5.45 2.65 <25 500 mesh (25 μm pore size) = 100% 0.96 Sample 2 23.43 0.78 <53 270 mesh (53μm pore size) = 100% 1.89 Sample 3 43.56 1.44 <75 200 mesh (75μm pore size) = 100% 2.84 Sample 4 22.31 1.67 <75 200 mesh (75μm pore size) = 100% 3.65 Comparative sample 1 5.34 3.23 <25 500 mesh (25 μm pore size) = 100% 0.89 Comparative sample 2 22.78 5.23 <53 270 mesh (53μm pore size) = 100% 1.76

[0089] According to Table 1 and Figure 1-5 The results are shown.

[0090] By comparing Example 1 with Comparative Example 1, it can be seen that when the mass ratio of the alkaline anion exchange resin to the raw material industrial alumina is less than 1:100 (0.9:100), that is, when the amount of alkaline anion exchange resin added is low, the removal effect of the uranium element is poor, and the uranium content of the comparative sample 1 (3.23 ppb) is significantly greater than the uranium content of sample 1 (2.65 ppb), and the uranium content of the comparative sample 1 exceeds 3 ppb.

[0091] By comparing Example 2 and Comparative Example 2, it can be seen that when the pH of the reaction system is greater than 2.5 (2.65), the removal effect of the uranium element will be significantly reduced, and the uranium content of the comparative sample 2 (5.23 ppb) is significantly greater than the uranium content of the sample 2 (0.78 ppb).

[0092] By comparing the thermal conductivity of EMC samples prepared from samples 1-3 and sample 4, it can be seen that the thermal conductivity of EMC samples can be significantly improved by compounding powders with multiple particle sizes to prepare EMC samples.

[0093] In addition, the spheroidization rate and true density of the low-radioactive spherical alumina particles of samples 1-4 were tested, and the spheroidization rate was ≥95%, and the true density was ≥3.65 g / cm 3 .

[0094] The above embodiments are only some preferred implementations of the present invention. It should be noted that the above preferred implementations should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A low-radioactive spherical alumina, characterized in that: The low-radioactive spherical alumina powder is α-alumina, with a uranium content of <3 ppb, a spheroidization rate of ≥95%, and a true density of ≥3.65 g / cm 3 ; Particle size D50 is 4.5~50 μm.

2. The low-radioactive spherical alumina according to claim 1, characterized in that: The powder particle size distribution of the low-radioactive spherical alumina has at least two peaks.

3. The low-radioactive spherical alumina according to claim 2, characterized in that: The low-radioactive spherical alumina powder has a maximum breaking particle size of less than 75 μm, and a particle size distribution D50 of 10-30 μm.

4. A method for preparing low-radioactive spherical alumina, characterized in that: The steps include: S1, using ultrapure water at 20-60°C, adding acid to adjust the pH to ≤ 2.5, to obtain an acid solution; S2, taking aluminum hydroxide / boehmite / industrial alumina as raw materials, adding them into the acid solution, stirring and dispersing, and obtaining a mixed slurry A; S3, adding a basic anion exchange resin to the mixed slurry A, hydrothermally stirring for 8 to 12 hours, removing the basic anion exchange resin, and obtaining a mixed slurry B; S4, filtering and drying the mixed slurry B, and heat-treating the dried material at 1300-1400° C. for 6-9 h; S5, crushing and dispersing the material after the heat preservation treatment in step S4, melting and spheroidizing at 1100-1300°C to obtain a crude low-radioactive spherical alumina product.

5. The method for preparing low-radioactive spherical alumina according to claim 4, characterized in that: The method further comprises step S6, wherein the crude low-radioactive spherical alumina product is subjected to airflow classification to obtain powders of various different cut-off particle sizes, and the powders of various different cut-off particle sizes are mixed and graded in proportion to obtain the desired low-radioactive spherical alumina product.

6. The method for preparing low-radioactive spherical alumina according to claim 4, characterized in that: The raw material is industrial aluminum hydroxide, and the mass ratio of the industrial aluminum oxide to the ultrapure water is 5-6:8-10.

7. The method for preparing low-radioactive spherical alumina according to claim 6, characterized in that: The uranium content in the industrial alumina is ≤40 ppb, and the particle size D50 is 0.5-45 μm; the industrial alumina is mainly γ-alumina.

8. The method for preparing low-radioactive spherical alumina according to claim 4 or 6, characterized in that: The alkaline anion exchange resin is a quaternary ammonium anion exchange resin; the addition ratio of the alkaline anion exchange resin to the alumina / boehmite / industrial alumina is 1-3:

100.

9. The method for preparing low-radioactive spherical alumina according to claim 4, characterized in that: In step S3, the alkaline anion exchange resin is placed in a filter bag / porous container and then put into the mixed slurry A for hydrothermal stirring treatment. After the treatment is completed, the filter bag / porous container containing the alkaline anion exchange resin is taken out to obtain a mixed slurry B.

10. The method for preparing low-radioactive spherical alumina according to claim 5, characterized in that: In step S6, three kinds of powders with a maximum breaking particle size of 25 μm and a D50 of 5.0-5.5 μm, a maximum breaking particle size of 53 μm and a D50 of 20-25 μm, and a maximum breaking particle size of 75 μm and a D50 of 40-45 μm are compounded in a mass ratio of 7:2:1 to obtain the desired low-radioactive spherical alumina product.

11. Use of low-radioactive spherical alumina prepared by the method for preparing low-radioactive spherical alumina as claimed in any one of claims 4 to 10 in EMC.

Citation Information

Cited By

  • Low-radioactivity spherical aluminum oxide for POP packaging and preparation method of low-radioactivity spherical aluminum oxide

    CN116924441A